PENGARUH REPUTASI PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN: SURVEI PEMBELI IPHONE DI TOKO PSTORE - Dendy Gustian (2021)
The corporate reputation becomes one of the consideration points by the consumer in making the decision to buy. Each corporate has its own reputation in terms of public perspective. Company reputation can be described as good and bad. The purpose of this research is to analyze how significant the influence of corporate reputation of unofficial smartphone store PStore on the iPhone's consumer buying decision. This research used the concepts of corporate reputation, price perception, and consumer buying decision. Also, the theory used The Corporate Reputation Theory. The method used is a quantitative method with the type of explanatory research. The location of this research is followers of Instagram account of @pst0re. The population in the study was 3.400.000 people using probability sampling techniques sampling of 99 respondents. To find out the relationships and influence of researchers using correlation tests and coefficient of determination. The results of this study indicate that the results of the research hypothesis prove that Ho was rejected and Ha was accepted. There was an influence of the Corporate Reputation on the iPhone's consumer buying decision. This research gives us information that the reputation is important and must be built properly, so that it can improve the company's image in the public eyes.